Pemberdayaan Remaja Sebagai Agen Kepemimpinan Kesehatan Masyarakat Berbasis Komunitas - Riyan Agus Faisal; Novica Jolyarni; Devi Nur Fitriyana (STIKES Columbia Asia Medan, 2025)
Youth empowerment is an effective strategy for improving the quality of community-based public health. As the nation's next generation, adolescents have great potential to become agents of change, including in the health sector. This study aims to develop a model for empowering adolescents as agents of public health leadership at the community level. The method used is a community-based participatory research approach involving adolescents, community leaders, and health workers. The results show that leadership training, health education, and social activities can increase the capacity of adolescents to lead and educate the community about clean and healthy living behaviors. The implementation of these activities also shows increased community participation and changes in health behaviors in the target environment. In conclusion, empowering adolescents as agents of community leadership can be a sustainable strategy for strengthening a public health system based on active participation.